INTEGRATED MODEL BASED ON EXTENDED FUZZY AHP AND CRITICALITY ANALYSIS FOR RISK ASSESSMENT IN CUSTOMS SUPPLY CHAIN: A PERSPECTIVE FROM MOROCCO - Hammadi, lamia; Souza de Curs, Eduardo; Ait Ouahman, Abdellah; Ibourk, Aomar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
The purpose of the current study is to assess risk in the customs supply chain. A risk assessment model using a combination of the extended fuzzy (EF) analytic hierarchy process (AHP) method with criticality analysis is proposed. EFAHP may be used as an efficient method for determining the importance of risks in the assessment process, but it does not determine whether the risks are at an acceptable level based on their risk points. A risk assessment study was conducted on Moroccan customs, in which threats were determined based on experience. The past 10 years’ statistical records were categorized, and each category was prioritized using the EFAHP method. EFAHP is a useful tool that considers the fuzziness of the data involved in determining the preferences for various decision variables. The fuzzy set theory gives a much better representation of the subjective judgments. Thus, it further refines the evaluation problem. The determined risks were also assessed based on criticality. The relation between the assessment of the risk class based on criticality and the fuzzy AHP weights was examined, and the risk class intervals for EFAHP were determined. In the study, an approach was developed based on the fact that the measure of the risk class in criticality risk assessment can be used with the obtained results, using the EFAHP method by comparing the obtained priority weights against the normalized scores of criticality. Therefore, the importance and classes of risks are determined.